Ecological Hermeneutics in Thabathaba’i’s Tafsir: the Relevance of The Caliphate Concept to the Contemporary Environmental Crisis - Siti Rohmah; Ahmad Mumtazul Faqih; Yusroh Yusroh; Nadia Nurpadilah; Khoirul Ropik Sidik; Andi Rosa (Ad-dawl : Jurnal Islamic Studies, 2026)
The global environmental crisis demands a renewed interpretation of religious moral sources, including the Qur’an, as a foundation for ecological ethics. This study explores the hermeneutical thought of Muḥammad Ḥusain Thabathaba’i in al-Mizan fi Tafsir al-Qur’an to examine the relevance of the Qur’anic concept of khalifah (vicegerent) in addressing contemporary ecological challenges. Methodologically, this research employs a qualitative, library-based approach with an ecological hermeneutic analysis that integrates Qur’anic self-interpretation (tafsir bi al-Qur’an), Sadrian rational philosophy, and modern environmental awareness. The findings reveal that in Thabathaba’i’s framework, humankind as khalifah is not an absolute ruler over nature but a guardian of cosmic balance, subject to divine law. His interpretation of verses such as Q.S. al-Baqarah [2]: 30, al-Rum [30]: 41, and al-A‘raf [7]: 56 indicates that environmental degradation stems from humanity’s deviation from its primordial role as God’s trustee. Therefore, Thabathaba’i’s hermeneutics can serve as a conceptual foundation for developing an Islamic environmental ethics grounded in spirituality and moral responsibility. This research contributes to Qur’anic studies by expanding the scope of Qur’anic hermeneutics toward ecological praxis, enriching Islamic eco-theology discourses, and offering an alternative epistemic response to the current global ecological crisis.